Efektivitas Blackgarlic Dalam Menurunkan Tekanan Darah Pasien Hipertensi di Puskesmas Simpang Tiga - Siska Mulyani; Siti Hafsyah Wahyuni; Afrida Harahap (HEALTH CARE : JURNAL KESEHATAN, 2021)
Hypertension is the cause of death with a figure of 23.7% of the total 1.7 million deaths in Indonesia. Prevention of hypertension can be overcome with non-pharmacological treatment, one of which uses Black garlic. Black garlic is a garlic product that has been fermented for a certain period of time at high temperatures and humidity. This type of research is quantitative which uses quasy experimental design with the one group pretest-postest approach. This research was conducted in the working area of Puskesmas Simpang Tiga Pekanbaru. The population in this study was all hypertension patients in the working region of Puskesmas Simpang Tiga Pekanbaru as many as 3,303 cases. Sampling using accidental sampling method as many as 15 people with hypertension. The results of the study obtained the average blood pressure of respondents after consuming black garlic dropped, which can be seen from the mean pretest and posttest systolic value of 152.40 dropped to 129.66, and the mean pretest and posttest diastolic values also dropped from 95.00 to 82.46 and the P-value value of 0.000. Black garlic is effective against lowering blood pressure (systolic and diastolic) before and after intervent